2013
DOI: 10.5194/isprsannals-ii-5-w2-139-2013
|View full text |Cite
|
Sign up to set email alerts
|

High precision target center determination from a point cloud

Abstract: ABSTRACT:Many applications of terrestrial laser scanners (TLS) require the determination of a specific point from a point cloud.In this paper procedure of high precision planar target center acquisition from point cloud is presented. The process is based on an image matching algorithm but before we can deal with raster image to fit a target on it, we need to properly determine the best fitting plane and project points on it. The main emphasis of this paper is in the precision estimation and propagation through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Algorithm: From the point cloud recorded by the laser scanner, the coordinates of the target are estimated by means of an algorithm. For this, there are multiple algorithmic approaches [26][27][28]. It is assumed that not all algorithms provide equally precise coordinates.…”
Section: Influencing Factors On the Precision Of Target Center Estimamentioning
confidence: 99%
“…Algorithm: From the point cloud recorded by the laser scanner, the coordinates of the target are estimated by means of an algorithm. For this, there are multiple algorithmic approaches [26][27][28]. It is assumed that not all algorithms provide equally precise coordinates.…”
Section: Influencing Factors On the Precision Of Target Center Estimamentioning
confidence: 99%
“…The ATOS target centers were processed simultaneously with data acquisition in the ATOS I software. TLS target centers were computed using an image matching algorithm (Kregar et al 2013). Using target coordinates the TLS and ATOS datasets are co-registered and transformed into a new coordinate system aligned with the joint plane.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The black-white targets included on the sample mounting board were needed to coregister the TLS and ATOS data in postprocessing. Highprecision TLS target centers were measured in the point cloud by applying an algorithm based on image matching (Kregar et al 2013) and ATOS target centers were identified automatically with built-in software.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Medians and robust standard deviations (robust STD) of height differences for the 11 scanning configurations are presented in Table 3. Negative median height differences indicate systematic co-registration errors, which result from uncertainties of TLS target centre estimation (Kregar et al 2013), but do not influence surface roughness values. The robust STD of dZ noisy values is an indicator of TLS noise level, and attenuates after range denoising is performed.…”
Section: Rock Surface Representationsmentioning
confidence: 99%